Analisis Kemampuan Calon Guru Matematika Dalam Menyusun Perangkat Pembelajaran - Bettisari Napitupulu; Agnes Teresa Panjaitan; Elsi Sirampun (Departement of Mathematics Education, 2024)
This study aims to the lesson-planning skills of prospective mathematics teachers. This research is a qualitative descriptive research. The data are student-created lesson plans. Upon reviewing these documents, the researcher focused on how well the objectives aligned with the learning model and the students’ worksheet. According to the study's findings, only one of the seven participants in selecting the cooperative learning model type STAD advanced to the group reward stage. Furthermore, one person selected STAD less accurate, as the materials would have been better suited for a cooperative learning model like TPS. students’ worksheet which is developed by students is in accordance with the syntax of the STAD type Cooperative learning model. Five students selected the TPS-type cooperative learning model; however, two of them made an incorrect choice because the difficulties materials had a rather high. There are 6 people who choose the Discovery Learning (DL) model, but the material to be taught is too difficult if students have to discover concepts by themselves. Only 1 student chose the PBL model but this model is not suitable for the material to be taught and learning does not begin by presenting problems.